Curative cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy in patients with peritoneal carcinomatosis and synchronous resectable liver metastases arising from colorectal cancer. Issue 1 (January 2017) - Lorimier, G.; Linot, B.; Paillocher, N.; Dupoiron, D.; Verrièle, V.; Wernert, R.; Hamy, A.; Capitain, O.
Abstract: Objectives: This study describes the outcomes of patients with colorectal peritoneal carcinomatosis (PC) with or without liver metastases (LMs) after curative surgery combined with hyperthermic intraperitoneal chemotherapy, in order to assess prognostic factors. Background: Cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC) increases overall survival (OS) in patients with PC. The optimal treatment both for PC and for LMs within one surgical operation remains controversial. Methods: Patients with PC who underwent CRS followed by HIPEC were evaluated from a prospective database. Overall survival and disease free survival (DFS) rates in patients with PC and with or without LMs were compared. Univariate and multivariate analyses were performed to evaluate predictive variables for survival. Results: From 1999 to 2011, 22 patients with PC and synchronous LMs (PCLM group), were compared to 36 patients with PC alone (PC group). No significant difference was found between the two groups. The median OS were 36 months [range, 20–113] for the PCLM group and 25 months [14–82] for the PC group ( p  > 0.05) with 5-year OS rates of 38% and 40% respectively ( p  > 0.05). The median DFS were 9 months [9–20] and 11.8 months [6.5–23] respectively ( p  = 0.04). The grade III–IV morbidity and cytoreduction score (CCS) >0 ( p  < 0.05) were identified as independent factors for poor OS. Resections of LMs and CCS >0 impair significantly DFS. Conclusions: Synchronous complete CRS of PC and LMs from a colorectal origin plus HIPEC is a feasible therapeutic option. The improvement in OS is similar to that provided for patients with PC alone.